Evaluation of TRMM precipitation radar rainfall estimates using NEXRAD and rain gauges in central and south Florida - Datta, Saswati; Roy, Biswadev; Jones, Linwood W.; Kasparis, Takis; Ray, Peter S.; Ding, Zhiyong; Charalampidis, Dimitrios (My University, 1999)
Monthly rate accumulation on 0.5° × 0.5° Lat/Lon boxes was estimated using Next Generation Radar WSR-88D (NEXRAD) and using rain gauges for the central Florida region during Texas/Florida Underflights Experiment (TEFLUN-B). The NEXRAD derived accumulation was within 45 mm rms of the individual boxes for a box average accumulation of 167 mm. For purposes of comparison, estimates of monthly average rain rate, on the same boxes, were made using NEXRAD and PR for both central and south Florida regions during the same period. It was found that the PR RainAllMean rain rate product does yield a reasonable estimate that is about a factor of 2 too high compared with the corresponding NEXRAD estimates. Comparisons with the PR RainMean product showed that they differ by a factor of 4 (PR greater than NEXRAD).